Entre o trabalhismo e o comunismo: projetos para o Brasil nas páginas dos jornais sergipanos, Fôlha Trabalhista e Fôlha Popular (1961 – 1964) - Santos, Railton Souza (2018)
This study emphasizes the exercise of power and its influence in society, based on two periodicals, Fôlha Trabalhista, linked to the Brazilian Labor Party Partido Trabalhista Brasileiro PTB, produced in the countryside of the State and Fôlha Popular, promoter of the actions of the political party PCB, that circulated in the capital from 1961 to 1964. It aims to understand the position of these periodicals in relation to the debate about the thinking and political actions of the forces such as the Left, (Laboring and Communism), focusing on the performance in the Sergipe State. This research is aimed by the methodology of the periodical criticism in its different parts, such as the social articles, newspaper articles, advertising, as well as the editorials focusing on national politics themes. This study emphasize that the press is the representation of reality and not the faithful portrait of reality, but of selected moments of reality, such as the process of selection of what is published in the newspapers is determined by their own journalistic criteria, which in turn are motivated by the political ideology in which the press is associated. It is important to emphasize that there were newspapers articles in 1962 that already denounced the eminence of a rightist coup. That would implement a terrorist dictatorship by the service of the most foreigner and national “infamous forces”, placing the economy in dependence on the United States.